Porous titanium felts as alternative metal gas diffusion layers for low temperature PEM fuel cells - Moydien, Mohamed (Department of Chemical Engineering, 2025)
Proton exchange membrane fuel cells(PEMFCs) use hydrogen to generate electrical energy with water as the only by-product, and are thus highlighted as a key energy conversion technology in the shift towards sustainable energy production. A key component of the PEMFC is the gas diffusion layer (GDL) which facilitates reactant transport and water management within the cell. The GDL is conventionally carbon-based which makes it susceptible to degradation during operation within the oxidative environment of the PEMFC. This experimental study investigates titanium fibre felts as an alternative cathode GDL material, applied and tested in a 25cm2 PEMFC. The study consists of: i) investigation of the felts varying in thickness from 200 µm to 1000 µm, ii) application of a hydrophobic treatment of 5 – 20 wt% polytetrafluorethylene (PTFE) to the best performing felt, and iii) application of a microporous layer (MPL) to the best performing felt. Within each work package, the GDL configurations are evaluated in terms of performance, mass transport properties, and water management, with comparison to conventional commercial carbon GDLs. The felts exhibited improved performance and flooding resistance relative to the carbon GDLs across thicknesses with optimisation at 400 µm. This was attributed to greater porosity which enhanced air permeability, as well as better ohmic resistance which remained low across thicknesses. Subsequently, a hydrophobic treatment of 5 wt% PTFE was shown to improve performance and flooding resistance of the 400 µm titanium felt relative to the untreated substrate and to comparable carbon GDLs due to enhanced hydrophobicity with minimal detriment towards porosity, gas permeability, and conductivity. Finally, it was shown that the addition of an MPL to the 400 µm felt with and without hydrophobic treatment did not improve performance beyond what was already achieved by the 400 µm felt with hydrophobic treatment. This comprehensive study of titanium fibre felt GDLs highlights their viability and benefit with current state-of-the-art carbon GDLs serving as a baseline for comparison.